Obszary chronione a rozwój regionalny - Kulczyk, Alina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Along with the development of civlisation, the views on the role of environment in economic processes have evolved. The 20th century brought new organisational and legal solutions for efficient protection of natural heritage. In Poland there are different ways of conservation and protection of the environment - the most important ones are: national parks, nature reserves, national scenic areas and protected landscape areas. Inclusion of protected areas into a group of factors stimulating or destimulating the regional development depends on the approach of local community. The area of protected areas in Poland and the world keeps growing and therefore it seems reasonable to support the trend for allowing business activities into the areas on condition that the activities are not harmful to the environment. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 59-65